2014
DOI: 10.1103/physreva.90.013822
|View full text |Cite
|
Sign up to set email alerts
|

Revealing quantum path details in high-field physics

Abstract: The fundamental mechanism underlying harmonic emission in the strong-field regime is governed by tunnel ionization of the atom, followed by the motion of the electron wave packet in the continuum, and finally by its recollision with the atomic core. Due to the quantum nature of the process, the properties of the electron wave packet strongly correlate with those of the emitted radiation. Here, by spatially resolving the interference pattern generated by overlapping the harmonic radiation emitted by different i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…In order to explore the interaction of the XUV pulse with the target gas, we use an ion microscope (IM) [37][38][39] to record the spatial distribution of the different photo ions in the XUV focus. More specifically, the IM records the y-projection of the ion distribution as a function of their time of flight (TOF) with single-ion sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore the interaction of the XUV pulse with the target gas, we use an ion microscope (IM) [37][38][39] to record the spatial distribution of the different photo ions in the XUV focus. More specifically, the IM records the y-projection of the ion distribution as a function of their time of flight (TOF) with single-ion sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In this context the harmonic spectrum is obtained by the Fourier transform of the time-dependent dipole moment which contains an integral over all possible electron trajectories characterized by ionization time (t i ), recombination time (t r ), and momentum p. Using a saddle-point analysis it can be shown that, for a given driving laser intensity I L , there are two interfering quantum [95][96][97][98][99] electron trajectories (the "Long" and the "Short" noted as L and S in the down panel of Figure 1b…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Normal incidence spherical mirrors with reflectivity 10%-20% have been used for focusing an XUV beam of~20 eV photon energy in the sub-4 µm level reaching intensities >10 13 W/cm 2 [150] while multilayer mirrors have been used for focusing an XUV beam of~90 eV photon energy [29]. This XUV focusing geometry has been extensively used for the temporal characterization of asec pulses via IR/XUV cross-correlation [29,97,146], 2nd-order autocorrelation approaches (using spit spherical mirror in unit 5 or spit silicon plates in unit 3) [45,47,48,50,54,97], and for imaging the ion distribution produced by linear and non-linear processes at the focus of the XUV beam [98,150]. In order to characterize the XUV beam after the interaction with the system under investigation, XUV diagnostics as those described in unit 4 can also be placed at the output of the 5th unit.…”
Section: Asec Beam Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The filter quality, in terms of IR transmission, was checked by means of an IR-XUV-beam profiler placed behind the filter foil, and the energy of the XUV radiation was measured using a calibrated XUV photodiode. The focus of the XUV beam in the detection area was characterized by means of an ion microscope detector [27]. The emitted XUV spectrum was recorded by measuring the energy-resolved photoelectron spectrum of the single-photon ionization of Xe.…”
Section: The Experimentsmentioning
confidence: 99%